Multi-interface WS2 / WO3 / PPy nano-composite wave-absorbing material as well as preparation method and application thereof

By using oxidation polymerization method to generate a conductive polymer layer on the WS2 surface, forming a nanocomposite absorbing material with multi-interface WS2/WO3/PPy, the problem of insufficient electromagnetic wave absorption performance of WS2 materials in the prior art is solved, and an efficient and low-cost electromagnetic wave absorption effect is achieved.

CN119684599AActive Publication Date: 2025-03-25NANJING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411550726.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-25
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The prior art has limitations in improving the electromagnetic wave absorption performance of two-dimensional tungsten disulfide (WS2) materials, especially by increasing dipole loss by manufacturing defects, which makes it difficult to significantly improve the dielectric loss capability, and the process is complex and costly.

Method used

An oxidation polymerization method is used to generate a conductive polymer layer on the WS2 surface, and the thickness of the conductive polymer layer is adjusted by adjusting the organic monomer content and reaction time to form a nanocomposite absorbing material with multi-interface WS2/WO3/PPy.

Benefits of technology

It significantly improves the conductivity and electromagnetic wave absorption performance of the material. The material is light in weight and low in cost, and is suitable for electrochemical devices and electromagnetic wave absorption shielding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684599A_ABST
    Figure CN119684599A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-interface WS2 / WO3 / PPy nano-composite wave-absorbing material as well as a preparation method and application of the multi-interface WS2 / WO3 / PPy nano-composite wave-absorbing material. According to the technical scheme, the conductive polymer layer is generated on the surface of the WS2 by using an oxidative polymerization method, the conductive polymer and the WS2 are subjected to structure and function design, and the thickness of the conductive polymer layer is regulated and controlled by regulating the content of the organic monomer and the reaction time, so that the microwave absorption performance is improved. The multi-interface WS2 / WO3 / PPy nano composite wave-absorbing material prepared on the basis of the thought shows excellent electric conductivity and EMW absorption performance. The WS2 / WO3 / PPy has the characteristics of light weight, low cost and good wave absorbing performance. The prepared wave-absorbing material can be used as a wave-absorbing agent, when the matching thickness is 2.3 mm, the effective absorption bandwidth can reach 6.72 GHz, and when the matching thickness is 3.3 mm, the minimum reflection loss can reach-55.87 dB. The film is prepared by mixing the graphene with cellulose, and the minimum reflection loss can reach-38dB under the condition that the thickness is 0.5 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nanomaterials, and in particular to a multi-interface WS2 / WO3 / PPy nanocomposite wave absorbing material. Background Art

[0002] With the rapid advancement of 5G technology and the increasing popularity of electronic devices, electromagnetic environment issues have become increasingly prominent. On the one hand, the security protection of personal information and the stable operation of precision equipment have put forward higher requirements for the equipment to resist external electromagnetic interference; on the other hand, the convenient use of daily electronic products and the intelligent development of wearable devices emphasize reducing the harm of electromagnetic radiation from the equipment itself. In view of this, it has become particularly urgent to seek an efficient and lightweight electromagnetic wave (EMW) absorption solution to balance the dual needs of electromagnetic protection and lightweight and intelligent equipment.

[0003] Two-dimensional tungsten disulfide (WS2) is a nanomaterial with a two-dimensional layered structure. Each layer is composed of tungsten and sulfur atoms arranged alternately, and the layers are connected by van der Waals interactions. The unique two-dimensional structure, large specific surface area and high reactivity have made it widely used in optoelectronic devices, sensors, catalysis and other fields, but the properties of semiconductors make it not a promising candidate for microwave absorbing materials. Wang Jing et al. synthesized flower-like WS2 nanomaterials by hydrothermal method. The abundant defects on the flower-like WS2 significantly increased the dipole polarization loss of the material, making the material exhibit excellent microwave absorbing performance (J. Wang, Y. Wang, J. Cheng, Y. Fu, Y. Li, W. Nie, J. Wang, J. Wang, B.Liu, D. Zhang, G. Zheng, M. Cao, Abundant vacancies induced highpolarization-attenuation effects in flower-like WS2 microwave absorbers, Journal of Materials Science&Technology 194 (2024).). However, the hydrothermal process limits the possibility of large-scale production of materials, and since this method only improves the dipole plan loss of the material by manufacturing defects, it is difficult to significantly improve the dielectric loss capacity of the material. Similarly, Liu Xudong et al. prepared NCFs@ WS2 composite materials by hydrothermal method and carbonization method. Although the composite materials showed good microwave absorption performance, the production cost of carbonization of the materials reduced the feasibility of large-scale application (X. Liu, S. Zhang, M. Yu, X. Zhao, Y. Jia, Y. Huang, M. Zong, WS2 nanosheets anchored on N-doped carbon fibers for superior electromagnetic wave absorption, Chemical Engineering Journal 465 (2023).). Summary of the invention

[0004] In order to make up for the defects of the prior art, the present invention provides a multi-interface WS2 / WO3 / PPy nanocomposite wave absorbing material and a preparation method thereof. The technical solution of the present invention is described as follows: A method for preparing a multi-interface WS2 / WO3 / PPy nanocomposite wave absorbing material comprises the following steps: S1, oxidation treatment of WS2 to obtain WS2 / WO3 containing heterogeneous interface; S2, adding the WS2 / WO3 prepared in S1 to water, dispersing evenly to obtain a WS2 / WO3 dispersion; adding the prepared WS2 / WO3 dispersion to a potassium persulfate solution, an ammonium persulfate solution, and a sodium persulfate solution, dispersing evenly, and then precooling at low temperature to obtain an oxidation solution; S3, adding the oxidizing liquid prepared in S2 to the pyrrole ethanol solution to carry out an oxidation reaction, and after the reaction is completed, filtering, washing and drying to obtain the multi-interface WS2 / WO3 / PPy nanocomposite absorbing material.

[0005] Preferably, the oxidation treatment in S1 is to heat WS2 from room temperature to 500-600°C at a heating rate of 10-15°C / min; and then calcine in air at 550-600°C for 15-30 min.

[0006] Preferably, the mass ratio of WS2 / WO3 to potassium persulfate solution, ammonium persulfate solution and sodium persulfate solution in the oxidizing solution S2 is 1:8~1:10.

[0007] Preferably, the low-temperature pre-cooling treatment in S2 is freezing the mixed solution at -100 to -80°C for 10 to 15 minutes.

[0008] Preferably, the mass ratio of WS2 / WO3 to pyrrole in the mixed solution of the pyrrole ethanol solution and the oxidizing solution in S3 is 1:1~1:5.

[0009] Preferably, the temperature of the oxidation reaction is 20-30° C., and the reaction time is 6-12 hours.

[0010] Preferably, the preparation method adopts the following steps: S1, WS2 was heated from room temperature to 500°C at a heating rate of 10°C / min; then calcined in air at 500°C for 30 min to obtain WS2 / WO3 containing a heterogeneous interface; S2, uniformly dispersing WS2 / WO3 in water to prepare 20 g / L WS2 / WO3 dispersion; dissolving potassium persulfate in water to prepare 120 g / L potassium persulfate solution; adding an equal volume of the prepared WS2 / WO3 dispersion to the prepared potassium persulfate solution, uniformly dispersing and freezing at -80°C for 10 min to obtain an oxidizing solution; S3, adding pyrrole to ethanol to obtain a 40g / L pyrrole ethanol solution; adding the oxidizing solution prepared in S2 to the pyrrole ethanol solution at a volume ratio of 2:1, and performing an oxidation reaction at 25°C for 6h to obtain the multi-interface WS2 / WO3 / PPy nanocomposite absorbing material.

[0011] The present invention provides an application of the multi-interface WS2 / WO3 / PPy nanocomposite wave absorbing material. The multi-interface WS2 / WO3 / PPy nanocomposite wave absorbing material has a WS2 / WO3 interface and a WO3 / PPy interface; The WS2 / WO3 interface is obtained by oxidizing the outer surface of WS2; the oxidation treatment is to heat WS2 from room temperature to 500-600°C at a heating rate of 10-15°C / min; and then calcine in air at 550-600°C for 15-30min; The WO3 / PPy interface is obtained by wrapping pyrrole on the surface of WS2 / WO3 through an oxidative polymerization method; the oxidative polymerization method is to mix WS2 / WO3 with potassium persulfate solution, ammonium persulfate solution, and sodium persulfate solution, place it in a -100~-80°C condition and freeze it for 10~15 minutes, and then carry out an oxidation reaction with pyrrole ethanol.

[0012] The present invention provides an application of a multi-interface WS2 / WO3 / PPy nanocomposite absorbing material, and the multi-interface WS2 / WO3 / PPy nanocomposite absorbing material is used for electromagnetic wave absorption and shielding.

[0013] Preferably, the multi-interface WS2 / WO3 / PPy nanocomposite absorbing material is mixed with cellulose in a mass ratio of 1:2 to 1:5 and then dispersed in water, and the absorbing film is prepared by a suction filtration method.

[0014] Beneficial Effects Compared with the prior art, we use the method of oxidative polymerization to generate a conductive polymer layer on the surface of WS2, design the structure and function of the conductive polymer and WS2, and adjust the thickness of the conductive polymer layer by adjusting the organic monomer content and reaction time, thereby improving the microwave absorption performance. The oxidative polymerization is a method of polymerizing organic monomers through an oxidation reaction at room temperature. Compared with traditional high-temperature polymerization, the oxidative polymerization method has the advantages of simple operation and energy saving and environmental protection. In the technical solution provided by the present invention, the reaction environment of the liquid phase at room temperature makes the conductive polymer have lower requirements on the chemical properties of the coating material. The multi-interface WS2 / WO3 / PPy nanocomposite absorbing material prepared based on the above ideas exhibits excellent conductivity and EMW absorption performance. The present invention has the following advantages: (1) The preparation method of the present invention is simple to operate, safe and controllable, and the surface polypyrrole of the prepared WS2 / WO3 is complete and uniform. The surface of the WS2 / WO3 coated with polypyrrole does not peel or fall off, and the whole is dark blue. The conductivity of WS2 / WO3 / PPy can reach 10 1S / m is 133% higher than that of WS2. Therefore, WS2 / WO3 / PPy is also suitable for electrochemical devices and other fields; (2) The advantages of the multi-interface preparation technology solution adopted in the present invention are: first, the process is simple and easy to operate. Since there are active sites on the surface of WS2 and the reaction activity is high, the WS2 / WO3 interface can be formed by calcining in air; second, the oxidative polymerization of polypyrrole can react at room temperature to form a conductive polymer layer with good conductivity; (3) The present invention wraps PPy on the surface of WS2 / WO3, and the two-dimensional layered structure and large specific surface area of ​​WS2 / WO3 allow more polypyrrole to be deposited on the surface. This not only improves its electrical conductivity, but also promotes the separation of charges in the electromagnetic field, thereby improving the polarization loss of the material. In addition, WS2 and WO3 inside the composite material form a non-uniform heterogeneous interface, which significantly improves the interface polarization loss and electromagnetic wave absorption performance of the material; (4) The present invention uses an oxidative polymerization strategy to prepare a WS2 / WO3 / PPy nanocomposite wave absorbing material. The WS2 / WO3 / PPy has the characteristics of light weight, low cost, and good wave absorbing performance, and can be used as a wave absorbing agent. According to tests, when the matching thickness of the material is 2.3 mm, the effective absorption bandwidth can reach 6.72 GHz; when the matching thickness of the material is 3.3 mm, the minimum reflection loss can reach -55.62 dB. When it is mixed with cellulose to prepare a film, the minimum reflection loss can reach -38dB under the condition of 0.5mm thickness. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the X-ray diffraction pattern of WS2 / WO3 obtained in step 1 of Example 1; Figure 2 This is the X-ray diffraction pattern of WS2 / WO3 / PPy-1 prepared in Example 1; Figure 3 Transmission electron microscope images of WS2 / WO3 prepared in step 1 of Example 1 and WS2 / WO3 / PPy-1 prepared in Example 1; Figure 4 The conductivity diagrams of WS2 / WO3 prepared in step 1 of Example 1 and WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3, and WS2 / WO3 / PPy-4 prepared in Examples 1 to 4; Figure 5 The wave absorption performance of WS2 / WO3 obtained in step 1 of Example 1, under the condition of matching thickness of 4.8 mm, the minimum reflection loss is -12.36 dB; Figure 6The wave absorption performance of WS2 / WO3 / PPy-1 prepared in Example 1, under the condition of matching thickness of 2.5 mm, the minimum reflection loss is -27.57 dB; Figure 7 The wave absorption performance of WS2 / WO3 / PPy-2 prepared in Example 2, under the condition of matching thickness of 4.1 mm, the minimum reflection loss is -47.68 dB; Figure 8 The wave absorption performance of WS2 / WO3 / PPy-3 prepared in Example 3, under the condition of matching thickness of 2.8 mm, the minimum reflection loss is -36.82 dB; Fig. 9 The wave absorption performance of WS2 / WO3 / PPy-4 prepared in Example 4, under the condition of matching thickness of 3.3 mm, the minimum reflection loss is -58.62 dB; Fig.10 This is an example diagram of preparing a cellulose absorbing film by compounding WS2 / WO3 / PPy-4 prepared in Example 4 with cellulose; Fig.11 The electromagnetic absorption performance of cellulose absorbing films prepared by compounding WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3 and WS2 / WO3 / PPy-4 obtained in Examples 1 to 4 with cellulose was measured. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified. Example

[0017] A multi-interface WS2 / WO3 / PPy-1 nanocomposite wave absorbing material, the preparation method of which comprises the following steps: (1) Preparation of WS2 / WO3: 2 g of WS2 solid was weighed and placed in a tube furnace, and heated in air at 500°C for 15 min to obtain WS2 / WO3 containing a heterogeneous interface; the WS2 was a two-dimensional WS2 (molecular weight of 247.97, purity >99.8%, particle size of 1-3 μm); (2) Prepare a dispersion: add 50 mL of deionized water to a beaker, weigh 1 g of the prepared WS2 / WO3 using an electronic balance, add it to the deionized water, place the beaker in an ultrasonicator and perform ultrasonic dispersion at 25°C for 1 h until the powder is evenly dispersed to obtain a well-dispersed WS2 / WO3 dispersion; (3) preparing an oxidizing solution, adding 50 ml of deionized water to a beaker, weighing 8 g of solid potassium persulfate using an analytical balance, adding and dissolving, and stirring to completely dissolve; adding the WS2 / WO3 dispersion prepared in step (2) to the potassium persulfate solution, stirring at 25°C for 30 min at a speed of 500 r / min; placing the above solution in a refrigerator and freezing at -80°C for 10 min to obtain an oxidizing solution; (4) Prepare a pyrrole ethanol solution and carry out an oxidative polymerization reaction. Use an analytical balance to weigh 1 g of pyrrole and add it to 50 ml of ethanol for dispersion. Place the oxidative solution prepared in step (3) into the pyrrole solution. Stir with an electromagnetic stirrer at 25° C. and a rotation speed of 500 r / min to carry out the oxidative polymerization reaction for 6 hours.

[0018] After the oxidative polymerization reaction is completed, the reaction product is repeatedly washed and filtered until the filtrate is colorless, and WS2 / WO3 / PPy-1 is finally obtained after drying.

[0019] X-ray diffraction and transmission electron microscopy were performed on the WS2 / WO3 prepared in step (1) of Example 1 and the WS2 / WO3 / PPy-1 prepared in Example 1. The results are as follows: Figures 1 to 3 As shown: Figure 1 This is the X-ray diffraction pattern of WS2 / WO3 prepared in step (1) of Example 1. From the figure, it can be seen that WS2 and WO3 have obvious diffraction peaks at the same time.

[0020] Figure 2 This is the X-ray diffraction pattern of WS2 / WO3 / PPy-1 in Example 1. The figure shows that WS2 / WO3 has obvious characteristic peaks after wrapping polypyrrole, and the characteristic peaks correspond to the PDF cards of WS2 and WO3, confirming that PPy is generated on the surface of WS2 / WO3.

[0021] Figure 3 The scanning electron microscope images of WS2 / WO3 prepared in step (1) of Example 1 and WS2 / WO3 / PPy-1 prepared in Example 1 are shown. The left image shows the unique two-dimensional layered structure of the WS2 / WO3 nanomaterial, and the right image shows that a layer of conductive polymer is formed on the surface of WS2 / WO3 after the polypyrrole reaction.

[0022] Example 2 A multi-interface WS2 / WO3 / PPy-2 nanocomposite wave absorbing material, the preparation method of which comprises the following steps: (1) Preparation of WS2 / WO3: 2 g of WS2 solid was weighed and placed in a tube furnace, and heated in air at 550°C for 15 min to obtain WS2 / WO3 containing a heterogeneous interface; the WS2 was a two-dimensional WS2 (molecular weight of 247.97, purity >99.8%, particle size of 1-3 μm); (2) Prepare a dispersion: add 50 mL of deionized water to a beaker, weigh 1 g of the prepared WS2 / WO3 using an electronic balance, add it to the deionized water, place the beaker in an ultrasonicator and perform ultrasonic dispersion at 25°C for 1 h until the powder is evenly dispersed to obtain a well-dispersed WS2 / WO3 dispersion; (3) preparing an oxidizing solution, adding 50 ml of deionized water to a beaker, weighing 8 g of solid potassium persulfate using an analytical balance, adding and dissolving, and stirring to completely dissolve; adding the WS2 / WO3 dispersion prepared in step (2) to the potassium persulfate solution, stirring at 25°C for 30 min at a speed of 550 r / min; placing the above solution in a refrigerator and freezing at -80°C for 10 min to obtain an oxidizing solution; (4) Prepare a pyrrole ethanol solution and carry out an oxidative polymerization reaction. Use an analytical balance to weigh 2 g of pyrrole and add it to 50 ml of ethanol for dispersion. Place the oxidative solution prepared in step (3) into the pyrrole solution. Stir with an electromagnetic stirrer at 25° C. and a rotation speed of 550 r / min to carry out an oxidative polymerization reaction for 6 hours.

[0023] After the oxidative polymerization reaction is completed, the reaction product is repeatedly washed and filtered until the filtrate is colorless, and WS2 / WO3 / PPy-2 is finally obtained after drying.

[0024] Example 3 A multi-interface WS2 / WO3 / PPy-3 nanocomposite wave absorbing material, the preparation method of which comprises the following steps: (1) Preparation of WS2 / WO3: 2 g of WS2 solid was weighed and placed in a tube furnace, and heated in air at 500°C for 30 min to obtain WS2 / WO3 containing a heterogeneous interface; the WS2 was a two-dimensional WS2 (molecular weight of 247.97, purity >99.8%, particle size of 1-3 μm); (2) Prepare a dispersion: add 50 mL of deionized water to a beaker, weigh 1 g of the prepared WS2 / WO3 using an electronic balance, add it to the deionized water, place the beaker in an ultrasonicator and perform ultrasonic dispersion at 20°C for 1 h until the powder is evenly dispersed to obtain a well-dispersed WS2 / WO3 dispersion; (3) preparing an oxidizing solution, adding 50 ml of deionized water to a beaker, weighing 8 g of solid potassium persulfate using an analytical balance, adding and dissolving, and stirring to completely dissolve; adding the WS2 / WO3 dispersion prepared in step (2) to the potassium persulfate solution, stirring at 20°C for 30 min at a speed of 600 r / min; placing the above solution in a refrigerator and freezing at -75°C for 10 min to obtain an oxidizing solution; (4) Prepare a pyrrole ethanol solution and carry out an oxidative polymerization reaction. Use an analytical balance to weigh 1 g of pyrrole and add it to 50 ml of ethanol for dispersion. Place the oxidative solution prepared in step (3) into the pyrrole solution. Stir with an electromagnetic stirrer at 25° C. and a rotation speed of 600 r / min to carry out the oxidative polymerization reaction for 10 hours.

[0025] After the oxidative polymerization reaction is completed, the reaction product is repeatedly washed and filtered until the filtrate is colorless, and WS2 / WO3 / PPy-3 is finally obtained after drying.

[0026] Example 4 A multi-interface WS2 / WO3 / PPy-4 nanocomposite wave absorbing material, the preparation method of which comprises the following steps: (1) Preparation of WS2 / WO3: 2 g of WS2 solid was weighed and placed in a tube furnace, and heated in air at 500°C for 30 min to obtain WS2 / WO3 containing a heterogeneous interface; the WS2 was a two-dimensional WS2 (molecular weight of 247.97, purity >99.8%, particle size of 1-3 μm); (2) Prepare a dispersion: add 50 mL of deionized water to a beaker, weigh 1 g of the prepared WS2 / WO3 using an electronic balance, add it to the deionized water, place the beaker in an ultrasonicator and perform ultrasonic dispersion at 25°C for 1 h until the powder is evenly dispersed to obtain a well-dispersed WS2 / WO3 dispersion; (3) preparing an oxidizing solution, adding 50 ml of deionized water to a beaker, weighing 8 g of solid potassium persulfate using an analytical balance, adding and dissolving, and stirring to completely dissolve; adding the WS2 / WO3 dispersion prepared in step (2) to the potassium persulfate solution, stirring at 25°C for 30 min at a speed of 550 r / min; placing the above solution in a refrigerator and freezing at -85°C for 10 min to obtain an oxidizing solution; (4) Preparing a pyrrole ethanol solution and conducting an oxidative polymerization reaction: using an analytical balance to weigh 2 g of pyrrole, adding it to 50 ml of ethanol for dispersion, placing the oxidative solution prepared in step (3) into the pyrrole solution, stirring with an electromagnetic stirrer at 25° C. and a rotation speed of 600 r / min, and conducting an oxidative polymerization reaction for 6 h.

[0027] After the oxidative polymerization reaction is completed, the reaction product is repeatedly washed and filtered until the filtrate is colorless, and WS2 / WO3 / PPy-4 is finally obtained after drying.

[0028] Example 5 The electromagnetic parameters of WS2 / WO3 prepared in step (1) of Example 1 and WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3, and WS2 / WO3 / PPy-4 prepared in Examples 1 to 4 were tested in the 2-18 GHz frequency band using a network analyzer (VNA, N5245A, Agilent, USA).

[0029] The WS2 / WO3 prepared in step (1) of Example 1 and the WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3, and WS2 / WO3 / PPy-4 prepared in Examples 1 to 4 were respectively mixed with paraffin wax at a mass ratio of 6:4 to prepare samples. All samples were pressed into the standard annulus ( f in : 3.04 mm, f out : 7.00 mm) to maintain geometric certainty. The thickness of all annuli was kept at 2.5 mm. Agilent PNA software automatically outputs relevant electromagnetic parameters based on the Nicolson and Ross and Weir algorithm. Figures 4 to 9 The results shown are: Figure 4 The results of the conductivity test of WS2 / WO3 prepared in step (1) of Example 1 and WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3, and WS2 / WO3 / PPy-4 prepared in Examples 1 to 4 are shown in the figure. The conductivity of WS2 / WO3, WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3, and WS2 / WO3 / PPy-4 are 0.08 S / m, 1.51 S / m, 3.62 S / m, 1.49 S / m, and 3.61 S / m, respectively. Figure 4 It can be seen that the conductivity of WS2 / WO3 is significantly enhanced after being coated with polypyrrole. The conductivity can be controlled by changing the mass ratio of pyrrole to WS2 / WO3. The thickness of polypyrrole coated on the surface of WS2 / WO3 increases with the increase of pyrrole addition.

[0030] from Figure 5~Figure 9It can be seen that the minimum reflection loss of WS2 / WO3 prepared in step (1) of Example 1 is -16.84 dB; the minimum reflection loss of WS2 / WO3 / PPy-1 is -27.57 dB; the minimum reflection loss of WS2 / WO3 / PPy-2 is -47.68 dB, the minimum reflection loss of WS2 / WO3 / PPy-3 is -36.82 dB; the minimum reflection loss of WS2 / WO3 / PPy-4 is -58.62 dB.

[0031] Example 6 1g WS2 / WO3 / PPy-4 and 2g cellulose were dispersed in 10ml water, and the cellulose absorbent film was prepared by suction filtration. Fig.10 As shown in the figure, it can be seen that WS2 / WO3 / PPy composite materials have the ability to be prepared into devices and have broad application prospects.

[0032] The electromagnetic parameters of cellulose absorbing films prepared by compounding WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3 and WS2 / WO3 / PPy-4 with cellulose were tested by network analyzer (VNA, N5245A, Agilent, USA) in the 2-18 GHz frequency band. The test results are shown in Fig.11 As shown in the figure, it can be found that the performance of the prepared cellulose absorbing film is positively correlated with the performance of the powder, that is, the better the filler performance, the better the electromagnetic wave absorption performance of the film.

[0033] In summary, the thickness of the conductive polymer can be adjusted, and by oxidizing WS2 in the air, the electromagnetic parameters of the composite material can be adjusted by changing the interface structure, thereby improving the microwave absorption performance. Comparative analysis of the test data of WS2 / WO3 / PPy-1, WS2 / WO3 / PPy-2, WS2 / WO3 / PPy-3 and WS2 / WO3 / PPy-4 in the embodiment shows that the increase in the thickness of polypyrrole can increase the conductivity of the composite material and the corresponding increase in the real part of the dielectric constant. At the same time, the internal oxidation time increases, forming an obvious heterogeneous interface, increasing the dielectric loss of the material, and further improving the electromagnetic absorption performance of the material.

[0034] It should be noted that, although the above embodiments have been described in this article, the patent protection scope of the present invention is not limited thereby. Therefore, based on the innovative concept of the present invention, changes and modifications made to the embodiments described herein, or equivalent structures or equivalent process changes made using the contents of the present invention specification and drawings, directly or indirectly applying the above technical solutions to other related technical fields, are all included in the patent protection scope of the present invention.

Claims

1. A multi-interface WS2 / WO3 / PPy nanocomposite absorbing material, characterized in that: The multi-interface WS2 / WO3 / PPy nanocomposite absorbing material has a WS2 / WO3 interface and a WO3 / PPy interface; The WS2 / WO3 interface is obtained by oxidation treatment of the outer surface of WS2; The WO3 / PPy interface is obtained by wrapping pyrrole on the surface of WS2 / WO3 through an oxidative polymerization method.

2. The multi-interface WS2 / WO3 / PPy nanocomposite absorbing material according to claim 1, characterized in that: The oxidation treatment is to heat WS2 from room temperature to 500-600°C at a heating rate of 10-15°C / min; then calcine in air at 550-600°C for 15-30min; And / or the oxidative polymerization method is to mix WS2 / WO3 with potassium persulfate solution, ammonium persulfate solution and sodium persulfate solution, place it in a -100~-80°C condition and freeze it for 10~15 minutes, and then carry out an oxidation reaction with pyrrole ethanol.

3. A method for preparing a multi-interface WS2 / WO3 / PPy nanocomposite wave absorbing material, characterized in that: The steps include: S1, oxidation treatment of WS2 to obtain WS2 / WO3 containing heterogeneous interface; S2, adding the WS2 / WO3 prepared in S1 to water, dispersing evenly to obtain a WS2 / WO3 dispersion; adding the prepared WS2 / WO3 dispersion to a potassium persulfate solution, an ammonium persulfate solution, and a sodium persulfate solution, dispersing evenly, and precooling to obtain an oxidation solution; S3, adding the oxidizing solution prepared in S2 to the pyrrole ethanol solution to carry out oxidation reaction for 6 to 12 hours to obtain the multi-interface WS2 / WO3 / PPy nanocomposite absorbing material.

4. The preparation method according to claim 3, characterized in that: The oxidation treatment in S1 is to heat WS2 from room temperature to 500-600°C at a heating rate of 10-15°C / min; then calcine in air at 550-600°C for 15-30min; And / or the pre-cooling treatment in S2 is freezing the mixed solution at -100~-80℃ for 10~15min.

5. The preparation method according to claim 3, characterized in that: The mass ratio of WS2 / WO3 to potassium persulfate solution, ammonium persulfate solution and sodium persulfate solution in the oxidizing solution S2 is 1:8~1:

10.

6. The preparation method according to claim 3, characterized in that: The mass ratio of WS2 / WO3 to pyrrole in the mixed solution of the pyrrole ethanol solution and the oxidizing solution described in S3 is 1:1~1:

5.

7. The preparation method according to claim 3, characterized in that: The preparation method adopts the following steps: S1, WS2 was heated from room temperature to 500°C at a heating rate of 10°C / min; then calcined in air at 500°C for 30 min to obtain WS2 / WO3 containing a heterogeneous interface; S2, uniformly dispersing WS2 / WO3 in water to prepare 20 g / L WS2 / WO3 dispersion; dissolving potassium persulfate in water to prepare 120 g / L potassium persulfate solution; adding an equal volume of the prepared WS2 / WO3 dispersion to the prepared potassium persulfate solution, uniformly dispersing and freezing at -80°C for 10 min to obtain an oxidizing solution; S3, adding pyrrole to ethanol to obtain a 40g / L pyrrole ethanol solution; adding the oxidizing solution prepared in S2 to the pyrrole ethanol solution at a volume ratio of 2:1, and performing an oxidation reaction at 25°C for 6h to obtain the multi-interface WS2 / WO3 / PPy nanocomposite absorbing material.

8. A multi-interface WS2 / WO3 / PPy nanocomposite absorbing material, characterized in that: The multi-interface WS2 / WO3 / PPy nanocomposite absorbing material is prepared according to the preparation method described in any one of claims 3 to 7.

9. An application of the multi-interface WS2 / WO3 / PPy nanocomposite absorbing material as claimed in claim 8, characterized in that: The multi-interface WS2 / WO3 / PPy nanocomposite absorbing material is used for electromagnetic wave absorption and shielding.

10. The use according to claim 9, characterized in that: The multi-interface WS2 / WO3 / PPy nanocomposite absorbing material is mixed with cellulose in a mass ratio of 1:2-1:5 and then dispersed in water, and an absorbing film is prepared by a suction filtration method.

Citation Information

Patent Citations

  • Tungsten disulfide-reduced graphene oxide three-dimensional self-assembly structure absorbing material

    CN109181638A

  • MXene / PPy composite wave-absorbing agent and preparation method thereof

    CN112292015A

  • Preparation method of low-frequency-band electromagnetic wave absorption WS2 / TiO2 hybrid material

    CN112919544A

  • Magnetic composite materials, methods of preparing magnetic composite materials, and electronic devices

    WO2024139811A1